Clinical manifestations and associated disorders in children with celiac disease in southern Iran - Mahshid Dehbozorgi; Naser Honar; Maryam Ekramzadeh; Forough Saki (BMC Pediatrics, 2020)
Abstract Background Celiac disease (CD) is an immune mediated inflammatory enteropathy, triggered by gluten exposure in HLA-DQ2 and/or –DQ8 genetics. The presentation of celiac disease in children is changing, with increase in non-classical symptoms. We aim to evaluate the clinical presentations of celiac disease amongst children, diagnosed with CD. Methods In this cross sectional study, we investigated the clinical features of 130 celiac patients at hospitals affiliated with Shiraz University of Medical Sciences. We used their hospital charts and conducted an interview with patients and their parents to find out demographic data, symptoms, laboratory, and histopathology findings for Marsh grading. Results Celiac disease was detected more amongst females (63.8%). We found that 5.4% of the patients had BMI more than 95th percentile. The most common GI symptoms were abdominal pain, flatulence and constipation. Also, the most common extra intestinal manifestation included bone pain, long term fatigue and anemia. Flatulence, chronic diarrhea, and paresthesia were observed more amongst male participants. The most common comorbidities were type 1 diabetes mellitus and hypothyroidism. Conclusion The most common gastrointestinal symptoms amongst our patients were abdominal pain, flatulence and constipation. Furthermore, the most common extra intestinal manifestations included bone pain, long term fatigue and anemia. The most associated comorbidities with CD in our children were type 1 diabetes mellitus and hypothyroidism.